Development of Community School Administration Model of Bang Khan Taek Subdistrict Administrative Organization, Samut Songkhram Province - waicharad, kanlayanee; Intarak, Choomsak (Journal of MCU Phetchaburi Review, 2026)
Abstract The purposes of research and development were to; study the problems in the administration of community schools in Bang Khan Taek Subdistrict Administrative Organization, Samut Songkhram Province, design and establish a community school management model, evaluate the community school management model, compare the experimental results before and after implementing the community school management model, and study the result of community school management model in terms of efficiency, effectiveness, and value. The informants consisted of administrator and teachers from Wat Sri Suwan Khongkharam (Rat Songkhro) School by purposive sampling, totaling 12 persons. The research tools included a questionnaire on management problems, a pre- and post-plan evaluation form, an evaluation form for the effectiveness, efficiency, and value of using the model, and a content validity assessment (IOC) for the effectiveness, efficiency, and value of using the model. The statistical methods used for data analysis included percentage, mean, standard deviation, t-dependent, and content analysis. The study found that the overall problem of school administration in community schools under the Bang Khan Taek Subdistrict Administrative Organization, Samut Songkhram Province was high level. The constructed community school management model consists of five steps: Personnel development, Information management, Learning management, Network participation, and Community knowledge sharing, namely “PILNS Model” The content validity assessment of the model revealed a consistency value ranging from 0.67–1.00, indicating its suitability for implementation according to the action plan. The experimental results showed that post-test scores were significantly higher than pre-test scores at the .01 level. Furthermore, the effectiveness, efficiency, and value of the model were rated at the highest levels. Keywords: Community School Administration Model, Bang Khan Taek Subdistrict Administrative Organization